2023
DOI: 10.1590/1983-40632023v5375552
|View full text |Cite
|
Sign up to set email alerts
|

Statistical downscaling in the TRMM satellite rainfall estimates for the Goiás state and the Federal District, Brazil

Abstract: Rainfall is a fundamental component of agricultural production, and knowing its potential and variability can ensure the success of this activity. However, the number of meteorological stations is still small, even in states with agricultural aptitude, such as Goiás. Geoprocessing techniques can be used to overcome this problem. Thus, this study aimed to evaluate the products of the Tropical Rainfall Measuring Mission (TRMM) satellite to describe the annual and monthly rainfall variability in the Goiás state a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, only two studies on equine leptospirosis have been performed in Goiás, and these were restricted to a few municipalities. In these studies, the frequency of the disease in horses and the prevalence of seropositive animals ranged from 14.4% [11] to 45.05% [12]. Thus, the results of the present study indicate a higher prevalence of seropositive animals than in previous studies, and this is the first study in which animals from the entire state were evaluated.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…However, only two studies on equine leptospirosis have been performed in Goiás, and these were restricted to a few municipalities. In these studies, the frequency of the disease in horses and the prevalence of seropositive animals ranged from 14.4% [11] to 45.05% [12]. Thus, the results of the present study indicate a higher prevalence of seropositive animals than in previous studies, and this is the first study in which animals from the entire state were evaluated.…”
Section: Discussionmentioning
confidence: 47%
“…Studies on seroprevalence and isolation have shown that horses are susceptible to a wide range of incidental infections, including serovars of the Pomona and Grippotyphosa serogroups, as well as the Icterohaemorrhagiae, Autumnalis, Sejroe, Canicola, and Ballum serogroups [2]. However, few studies have evaluated the prevalence of leptospirosis in horses in the Central-West region of Brazil and in the state of Goiás, located in the tropical savanna (Cerrado), data on the seroprevalence of equine leptospirosis are scarce and restricted to a few municipalities [11,12]. Thus, the aim of the present study was to determine the seroprevalence of Leptospira spp.…”
Section: Introductionmentioning
confidence: 99%